2014
DOI: 10.1021/ma500956b
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of Cadmium Sulfide Nanoparticles within Polystyrene Melts

Abstract: We present a detailed study of the dynamics of cadmium sulfide nanoparticles suspended in polystyrene homopolymer matrices using X-ray photon correlation spectroscopy for temperatures between 120 and 180 °C. For low molecular weight polystyrene homopolymers, the observed dynamics show a crossover from diffusive to hyper-diffusive behavior with decreasing temperatures. For higher molecular weight polystyrene, the nanoparticle dynamics appear hyperdiffusive at all temperatures studied. The relaxation time and ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 61 publications
0
20
0
Order By: Relevance
“…At great distances from qnormal* (q > 0.025 Å −1 ), the noisy intensity correlation compromised any meaningful measurements of g2 and the corresponding τ. Theoretical and experimental studies have shown that many types of highly structured but disordered soft matter exhibit slow relaxation with hyperdiffusive dynamics. Two concepts have been proposed to explain hyperdiffusion.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…At great distances from qnormal* (q > 0.025 Å −1 ), the noisy intensity correlation compromised any meaningful measurements of g2 and the corresponding τ. Theoretical and experimental studies have shown that many types of highly structured but disordered soft matter exhibit slow relaxation with hyperdiffusive dynamics. Two concepts have been proposed to explain hyperdiffusion.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, we cannot confirm the model that is suitable to analyze the current results. However, slow relaxation with hyperdiffusive dynamics are often investigated via the SFR model . Therefore, we utilized the SFR model to analyze the current study.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations